2010
DOI: 10.1007/s10071-010-0345-6
|View full text |Cite
|
Sign up to set email alerts
|

Do birds (pigeons and bantams) know how confident they are of their perceptual decisions?

Abstract: Rhesus monkeys are known to recognize confidence about their immediate perceptual and cognitive decisions by using a betting procedure (Son and Kornell in The missing link in cognition: origins of self-reflective consciousness. Oxford University Press, New York, pp 296-320, 2005; Kornell et al. in Psychol Sci 18:64-71, 2007). In this report, we examined whether this ability is shared in two avian species (pigeons and bantams) in order to know how widespread this metacognitive ability is among animals. We train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Beyond the primates, data exist only for a dolphin (Smith, Schull, Strote, McGee, Egnor, & Erb. 1995), rats (Foote & Crystal, 2007, 2012), bantams (Nakamura, Watanabe, Betsuyaku, & Fujita, 2011) and pigeons (Adams & Santi, 2011; Castro & Wasserman, 2013; Iwasaki et al, 2013; Nakamura et al, 2011; Roberts et al, 2009; Sole, Shettleworth, & Bennett, 2003; Sutton & Shettleworth, 2008; Zentall & Stagner, 2010). Even within the primates, researchers have mainly tested rhesus monkeys and apes, with some assessments of capuchin monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the primates, data exist only for a dolphin (Smith, Schull, Strote, McGee, Egnor, & Erb. 1995), rats (Foote & Crystal, 2007, 2012), bantams (Nakamura, Watanabe, Betsuyaku, & Fujita, 2011) and pigeons (Adams & Santi, 2011; Castro & Wasserman, 2013; Iwasaki et al, 2013; Nakamura et al, 2011; Roberts et al, 2009; Sole, Shettleworth, & Bennett, 2003; Sutton & Shettleworth, 2008; Zentall & Stagner, 2010). Even within the primates, researchers have mainly tested rhesus monkeys and apes, with some assessments of capuchin monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Also, recently, observers have been asked to place a wager on the accuracy of their decision, either with the possibility that the reward is lost if the wager is incorrect (Persaud, McLeod, & Cowey, 2007) or without the risk of losing the wager (Dienes & Seth, 2010). Since wagering is independent of speech, it has been used successfully to explore awareness in animals-specifically, in monkeys (Kornell, Son, & Terrace, 2007) and pigeons (Nakamura, Watanabe, Betsuyaku, & Fujita, 2011). A third approach asks the observers to make judgments directly about their visual experiences.…”
Section: Objective Versus Subjective Measuresmentioning
confidence: 99%
“…However, rhesus monkeys and rats can provide other responses that reflect the monitoring of uncertainty of their perceptual experiences (Beran, Smith, Redford, & Washburn, 2006; Foote & Crystal, 2007, 2012; Shields, Smith, & Washburn, 1997; Smith, Beran, Redford, & Washburn, 2006; Smith, Redford, Beran, & Washburn, 2010; Smith, Schull, Strote, McGee, Egnor, & Erb, 1995; Smith, Shields, Schull, & Washburn, 1997) and pigeons, rhesus monkeys, and orangutans provide responses that reflect monitoring of memory (Adams & Santi, 2011; Basile, Hampton, Suomi, & Murray, 2009; Fujita, 2009; Hampton, 2001; Hampton & Hampstead, 2006; Inman & Shettleworth, 1999; Smith, Shields, Allendoerfer, & Washburn, 1998; Suda-King, 2008; Suda-King, Bania, Stromberg, & Subiaul, 2013; Sutton & Shettleworth, 2008; Templer & Hampton, 2012). Rhesus monkeys, chimpanzees, orangutans, and pigeons have demonstrated the ability to search for needed information (Beran & Smith, 2011; Beran, Smith, & Perdue, 2013; Call, 2010; Call & Carpenter, 2001; Castro & Wasserman, 2013; Hampton, Zivin, & Murray, 2004; Iwasaki, Watanabe, & Fujita, 2013; Kirk, McMillan, & Roberts, 2014; Marsh & MacDonald, 2012a, 2012b; Roberts et al, 2009), and have even shown the capacity to make confidence judgments about the outcomes of already completed responses, although only with extensive training (Kornell, Son, & Terrace, 2007; Morgan, Kornell, Kornblum, & Terrace, 2014; Nakamura, Watanabe, Betsuyaku, & Fujita, 2011; Shields, Smith, Guttmannova, & Washburn, 2005). …”
mentioning
confidence: 99%
“…The monkeys tended to bet high more often on trials that were correct and low more often on trials that were incorrect. Once trained on how these icons operated, the monkeys transferred this appropriate use of the icons to new tasks assessing different forms of perception and memory (see also Morgan et al 2014; Nakamura et al, 2011). Shields et al (2005) compared the performance of rhesus monkeys to that of humans in another task that required a betting response about the perceptual classification that had just been made.…”
mentioning
confidence: 99%